Herbal medicines based on a black cohosh extract as a safe alternative for the correction of menopausal symptoms - I V Kuznetsova (Гинекология, 2014)
The review deals with the effectiveness and safety of plant hormones in the treatment of menopausal syndrome. Particular attention is given to black cohosh extract as a drug with distinction from other drugs in this group thanks to its action spectrum. The results of modern studies show that black cohosh extract is not so much phytohormonal as a natural vegetotropic agent that mediates its effect through serotonergic receptors. High-performance of black cohosh extract in relieving vasomotor symptoms is confirmed by comparative, placebo-controlled trials. However, no direct interaction with estrogen receptors defines security of black cohosh extract use. Long-term use of drugs based on black cohosh extract has no effect on the endometrium proliferative processes and mammary glands. Use of black cohosh extract can be considered a viable alternative to hormone replacement therapy in cases where it is impossible or undesirable.